Literature Review on the Nature of Learners In the Philosophy of Islamic Education - Neng Nurcahyati Sinulingga; Usiono Usiono; Erni Suyani; Amsal Qori Dalimunthe (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
T This article analyzes the nature of learners in Islamic education philosophy that can be implemented holistically in modern education. This research aims to explore the concept of learners in the perspective of Islamic education philosophy, the challenges of its application in the modern curriculum, and the influence of this philosophy on the character building of learners in the era of globalization. The method used in this article is the systematic literature review (SLR) method by collecting data from books, journals, and scientific articles published between 2016 and 2023 through the Google Scholar and Publish or Perish platforms to ensure the validity and relevance of the sources. Furthermore, the results of the discussion in this study show that (1) the concept of learners in Islamic education philosophy emphasizes the development of intellectual, moral, and spiritual potential in a balanced manner, which aims to create individuals with intellectual intelligence, praiseworthy morals, and spiritual awareness; (2) the main challenge in the modern curriculum is the lack of integration of Islamic values, which hinders the character building of learners in the midst of a moral crisis; (3) Islamic education philosophy is important to shape the character of learners to be able to face globalization without losing Islamic identity. The integration of Islamic values in modern education creates learners who are intelligent, noble, and contribute positively to societ